2016
DOI: 10.18261/issn.1891-943x-2016-04-01
|View full text |Cite
|
Sign up to set email alerts
|

Fun and games - Finnish children’s ideas for the use of digital media in preschool

Abstract: This study has used drawings from and interviews with 5-6 year-old Finnish children (N=103) to explore their ideas for the use of digital media in preschool. The main findings, based on data driven analysis, were the following: Playing commercial digital games was the most popular activity followed by media production, mainly photographing. Computers, tablets and cameras were the most popular devices. Digital media was understood to be more about leisure than learning. Pedagogical implementations are discussed. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…1 January 2010 through 31 December 2017 The time scope was chosen for the perception that this era has been the most productive for technology integration research done in the context of early childhood education (Mertala, 2016). This phenomenon is-at least in part-explained by the proliferation of digital technologies in kindergartens during the 2010s (Blackwell, Wartella, Lauricella, & Robb, 2015).…”
Section: Time Scopementioning
confidence: 99%
“…1 January 2010 through 31 December 2017 The time scope was chosen for the perception that this era has been the most productive for technology integration research done in the context of early childhood education (Mertala, 2016). This phenomenon is-at least in part-explained by the proliferation of digital technologies in kindergartens during the 2010s (Blackwell, Wartella, Lauricella, & Robb, 2015).…”
Section: Time Scopementioning
confidence: 99%
“…Mertala [23] conducted a study about the ideas and wishes of children about using digital media and games in preschool. The types of digital technologies studied were computers, tablets, cameras, and television.…”
Section: Digital Technologiesmentioning
confidence: 99%
“…Thus, they should be offered alternative mediums for self-expression for ensuring rich data. The use of visual methods and materials, such as drawing and pictures, is typical in contemporary childhood research (Lipponen, Rajala, Hilppö, & Paananen, 2016), and this has proven to provide rich data for exploring young children's meaning making around digital technologies (Brito et al, 2018;Mertala, 2016Mertala, , 2019Robertson et al, 2017). In this study, visual materials were used as supports for verbal narration (pictures shown to children) and forms of visual narration (drawing task).…”
Section: Participants Research Context and Data Collectionmentioning
confidence: 99%
“…In this study, visual materials were used as supports for verbal narration (pictures shown to children) and forms of visual narration (drawing task). From a sociocultural viewpoint, children's drawings do not emerge in a "cultural vacuum" (Mertala, 2016), but instead, they are always influenced by the communication and symbol systems around them (Anning & Ring, 2004).…”
Section: Participants Research Context and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation